I, robot - Asimov, Isaac, 1920-1992. (New York : Bantam Books, 1991)
Dr. Susan Calvin, the first great practitioner of the new science of robopsychology in 2008, looks back on her career with U.S. Robotics on the occasion of her retirement fifty years later, telling stories of how the mechanical race developed.
Wilson's Fiction.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Robots -- Fiction; Science fiction; Robots -- Fiction; Science fiction